The antecedents of export performance of Brazilian small and medium-sized enterprises (SMEs): the non-linear effects of customer orientation - Lengler, J. (2016)
This article examines the determinants of customer orientation and the quadratic effects of customer orientation on export performance. The relationship between customer orientation and export performance has been assumed to have a linear relationship, neglecting the possibility of non-linear relationships. While most studies have been conducted in developed countries, we test our model in Brazil, an emerging market economy. The findings suggest that technology intensity and competitive intensity are key determinants in explaining success in an export market. Our findings also indicate that the relationship between customer orientation and export performance is quadratic (U-shaped) rather than linear. The implications of these findings are discussed.